USE OF MODERN-INNOVATIVE PROGRAMS IN TEACHING FOREIGN LANGUAGES - Hasanova Yu.Z; Kochkorova O.M. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article deals with one of the problems of modern teaching - the use of interactive methods to deepen the study of foreign languages and the formation of knowledge, skills, and abilities of students in the process of teaching.